الأزمة الأوكرانية – الروسية وتأثيرها على العلاقات الدولية - أ.محمود محمد الحراري (Aljameai, 1970)
المستخلص:يدرس البحث الأزمة الروسية الأوكرانية كأزمة دولية بالغة الأهمية والتعقيد من خلال الوقوف على اهم خلفياتها واسبابها من ثم التعرف على أبرز مساراتها واطرافها الرئيسية والثانوية ومعرفة مضامين قراراتهم ومنطلقاتهم اتجاه الأزمة وصولا للبحث في تداعياتها الجسيمة التي انعكست سلبا على  مسار العلاقات الدولية والدبلوماسية لمختلف الدول حتى يحقق البحث نتائجه المرجوة بالوصول لتحليلات منطقية على أسس موضوعية سليمةAbstract:The research studies the Russian- Ukrainian crisis as an international crisis of great importance and complexity by examining its most important backgrounds and causes, then identifying its most prominent paths and its main and secondary parties and knowing the contents of their decisions and starting points towards the crisis, leading to researching its grave repercussions that negatively affected the course of international and diplomatic relations for various countries until the research achieves Its desired results by reaching logical analyzes on sound objective ground.